Role of videolaparoscopy in diagnosis and treatment of postoperative complications in abdominal surgery - B.O. Matviychuk; R.L. Bokhonko; A.M. Lavryk; O.B. Matviychuk; A.D. Kvit; M.М. Budnyk; T.V. Pyvovar (Медицина неотложных состояний)
Background. Laparoscopic operations become a priority in abdominal surgery, having a number of advantages over open interventions. For a long time, relaparotomy was and remains the main method for management of postoperative complications. The role and effectiveness of relaparoscopy in eliminating complications remain unstudied. Aim: to find out the effectiveness and expediency of relaparoscopy in management of post-laparoscopic complications. Materials and methods. A retrospective analysis of treatment outcomes in laparoscopic surgeries was carried out, of which 943 (48.8 %) were elective and 988 (51.2 %) were urgent. Most patients who underwent elective procedures (551 (58.4 %)) had chronic calculous cholecystitis. Four-port method was used in 547 cases, single-port — in 4 (0.7 %). Four hundred and twenty-one laparoscopic cholecystectomy was performed urgently for blocked gallbladder, local or diffuse peritonitis. Laparoscopic appendectomy was caried out in 445 patients. Acute adhesive obstruction of the small intestine was resolved laparoscopically in 122 patients: mechanical — in 83, strangulated — in 39. Adhesiolysis was done in 122 patients with adhesive obstruction. Laparoscopic herniotomy and allohernioplasty were performed in 39 patients, of which 21 procedures were inguinal, 13 — umbilical and 5 — postoperative. Sleeve resections were carried out in 10 morbidly obese individuals. In 126 cases, main purpose of laparoscopic surgery was: evaluation of spread of malignant tumor, biopsy of metastases, lymph node biopsy for pathomorphological examination. Results. Postoperative complications arose in 53 (2.7 %) laparoscopically operated patients (0.8 % after elective interventions and 1.9 % after urgent ones): internal bleeding — 16 (0.8 %), biliary leakage into abdominal cavity — 13 (0.6 %), early adhesive obstruction of the small intestine — 11 (0.5 %), abscess/peritonitis — 13 (0.6 %). Relaparotomy was performed in 7 patients (0.3 %): in 4 (0.2 %) of them, after elective and in 3 (0.1 %) after urgent procedures, mostly due to unstable hemodynamics and septic condition. There were no fatal cases in this group. Relaparoscopy for diagnosis and elimination of postoperative complications was used in 28 (1.4 %) cases, of which 10 (0.5 %) after elective procedures and 18 (0.9 %) after emergency surgeries, without mortality. Conversion to open surgery after relaparoscopy was done in 16 (57.1 %) patients, mostly due to difficulties in verifying the viability of intestine and for hemostasis. Two (12.5 %) patients died due to multiple organ failure, sepsis, pulmonary embolism. Conclusions. 1. Relaparoscopy is an effective method of diagnosis and elimination of post-laparoscopic complications. 2. Relaparoscopy is advisable only in hemodynamically stable patients. 3. Relaparoscopy with conversion leads to worst results in patients with postoperative complications.